Perbandingan Metode Hierarchical Cluster Analysis untuk Analisis Keragaman Hayati Trypanosoma evansi dari Indonesia Berdasarkan Profil Protein (COMPARISON OF HIERARCHICAL CLUSTER ANALYSIS METHODS FOR BIODIVERSITY ANALYSIS OF TRYPANOSOMA EVANSI - Subekti, Didik Tulus; Yuniarto, Ichwan; Sulinawati, Sulinawati (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.516, 2018)
Hierarchical Clustering Analysis (HCA) has long been known to be useful for the analysis of biodiversity of microorganisms based on SDSPAGE protein profile (sodium dodecyl sulfate polyacrylamide gel electrophoresis). However, varying methods of HCA consequently produce variability of analysis results and interpretations. Therefore, it is necessary to evaluate and further determine the most appropriate method which could described the biodiversity based on protein profiles of T.evansi isolates from Indonesia. Eleven isolates of T.evansi from different geographic locations were run on SDS PAGE. Furthermore, SDS PAGE protein profiles from eleven isolates were converted into binary data and analyzed using five different methods of HCA i.e. Average Linkage, Complete Linkage, Single Linkage, Ward Linkage and McQuitty Linkage, respectively.Data were also analyzed by multidimensional scaling (MDS) and densitogram. The analysis showed that the dendrogram constructed with Ward Linkage gives the best results and corresponding with densitogram, MDS and able to describe the geographical origins of isolates.
Keywords: Trypanosoma evansi, keragaman hayati, dendrogram, profil protein, SDS PAGE